1965
DOI: 10.1021/jf60140a005
|View full text |Cite
|
Sign up to set email alerts
|

Forage Analysis, Carbohydrate Content in Alfalfa Herbage as Influenced by Methods of Drying

Abstract: changes and accelerated respiratory losses similar to those occurring during waiting (12).Changes that may occur in the content of some carbohydrate constituents during the drying and preservation of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

1972
1972
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…This suports the claim of "ruggedness" made for the iodified acid detergent fibre method by Collier : Foulds (1975). The consistently low WSC alues in oven-dried material agree with reports y Jones (1962) and Raguse & Smith (1965).…”
Section: Discussionsupporting
confidence: 88%
“…This suports the claim of "ruggedness" made for the iodified acid detergent fibre method by Collier : Foulds (1975). The consistently low WSC alues in oven-dried material agree with reports y Jones (1962) and Raguse & Smith (1965).…”
Section: Discussionsupporting
confidence: 88%
“…The sum of these three fractions was termed for practical reasons TNC in this paper. In the laboratory, samples were oven-dried at 100°C for 60 min and then at 70°C for 48 h. This procedure minimizes respiratory losses when a great number of samples prevents their immediate analysis (Raguse and Smith 1965). In previous assays with lugol solution (Sigma), we observed that starch accumulation in the lignotuber occurred only in the external, live tissues, whereas the central lignified tissues were depleted of it.…”
Section: Determination Of Carbohydrate Concentrationsmentioning
confidence: 99%
“…For preservation of carbohydrates, fine root samples were immediately placed on ice, then oven-dried at 100°C for 90 min that day, followed by oven-drying at 65°C until reaching constant mass (Raguse and Smith 1965). Dried root biomass was hand-sorted free of remaining planting media particles and re-dried at 65°C, weighed, ground to a fine powder, and stored in the dark in a dessicator until carbohydrate analysis.…”
Section: Measurementsmentioning
confidence: 99%